Reactions of Hexaphenyldilead with Bifunctional Tetradentate Schiff Bases - BANSAL, DEEPIKA; MOHAN, MAN; MITTAL, R.K. (Asian Journal of Chemistry, 2010)
The reactions of hexaphenyldilead with bifunctional tetradentate Schiff bases in 1:1 molar ratio were studied in anhydrous benzene. Complexes of the type [R3Pb]1-S'B' (where R = -C6H5 and S'B' is Schiff base) have been synthesized. All the reactions were found to be quite facile and lead-lead bond was found to be cleaved in preference to the lead-carbon bond. The resulting derivatives of organolead(IV) were obtained in the form of yellow solids. They were quite stable in air and are not easily attacked by moisture. They are soluble in DMF and DMSO. The molar conductance values in DMSO were found to be below 5 ohm-1 cm-2 mol-1 indicating the absence of any ionic species. In these complexes, the lead atom probably acquires coordination number of 5 and exhibits trigonal bipyramidal configuration.